Flame-retardant nylon material and preparation method thereof

By using modified polyhedral oligosilsesquioxane and its derivatives as flame retardant synergists in nylon materials, combined with PA, toughening agent, P- and N-type flame retardant, halogen-free flame retardant nylon materials are formed, which solves the problem of poor flame retardant nylon materials and significantly improves flame retardant performance and physical and mechanical properties.

CN119752160AActive Publication Date: 2025-04-04SHENZHEN WOER HEAT SHRINKABLE MATERIAL

Patent Information

Application Number
CN202411993196.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing nylon materials lack flame retardant properties, which makes them flammable in high temperature environments, and the large amount of flame retardant added will reduce the mechanical properties of the material.

Method used

By using the modified polyhedral oligosilsesquioxane and its derivatives as flame retardant synergists together with PA, toughening agent, P-based flame retardant and N-based flame retardant, a halogen-free flame retardant nylon material is formed. During the combustion process, the material significantly improves the flame retardant performance by forming a carbon layer, a ceramic barrier layer and a glass-like protective film.

Benefits of technology

It significantly improves the flame retardant performance, crack resistance and physical and mechanical properties of the material, while maintaining the good processing and flame retardant performance of the thermoplastic elastomer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752160A_ABST
    Figure CN119752160A_ABST
Patent Text Reader

Abstract

The invention discloses a halogen-free flame-retardant nylon material which comprises PA (polyamide), a toughening agent, a P-series flame retardant, an N-series flame retardant, modified polyhedral oligomeric silsesquioxane and a derivative flame-retardant synergist of the modified polyhedral oligomeric silsesquioxane. The modified polyhedral oligomeric silsesquioxane and the derivative flame-retardant synergist thereof contain boron, an annular structure R2 with the carbon hydrogen ratio larger than 1 and two inorganic silicon cage cores, and the structures form a carbon layer, a ceramic barrier layer, a protective film or a heat-insulation coke layer and other protective layers in the combustion process, so that the anti-dripping effect is greatly improved, and meanwhile, the anti-dripping effect is greatly improved. Heat and oxygen transfer is isolated, combustible gas release is reduced, and the flame retardant property of the material is remarkably improved under the combined action of multiple mechanisms. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and the derivative of the modified polyhedral oligomeric silsesquioxane is matched with the P-series flame retardant and the N-series flame retardant to realize synergistic flame retardance, so that the flame retardant property of the flame-retardant nylon material is improved while the dosage of the flame retardant is reduced. The halogen-free flame-retardant nylon material provided by the invention is excellent in flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a halogen-free flame-retardant nylon material. Background Art

[0002] Polyhedral oligomericsilsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.

[0003] Nylon (PA) materials are a type of polymer materials with strong polarity. Hydrogen bonds can be formed between molecules, so the melting temperature is high, the melting temperature range is narrow, and there is a clear melting point. It is widely used in various industries. However, since nylon materials do not have flame retardant properties, flame retardant modification of nylon has become a new direction for nylon materials. At present, there are two main flame retardant modifications of nylon: chemical modification and physical modification. Chemical flame retardant modification is to introduce flame retardant components into the main chain or side chain of nylon through chemical reactions, so that the molecular chain itself can have flame retardant properties. Physical flame retardant modification is to introduce flame retardant components or flame retardants into the nylon matrix, and prepare flame retardant modified nylon materials through mixed granulation. Flame retardant modification by blending is the most convenient and widely used method. The flame retardant melamine polyphosphate (MPP) is a relatively ideal flame retardant for nylon. Its chemical composition elements are similar to nylon and it has good compatibility with the nylon matrix. At the same time, melamine polyphosphate molecules contain nitrogen and phosphorus elements, and have high flame retardant efficiency. Alkyl phosphinates, melamine polyphosphates, etc. are used as flame retardants, and nylon is used as the matrix through melt blending in an extruder to obtain flame retardant and antistatic nylon materials. Although this method can produce flame retardant and antistatic nylon, the amount of flame retardant melamine polyphosphate added is large, and the introduction of more flame retardants will reduce the mechanical properties of the material. Therefore, it is very necessary to develop a halogen-free flame retardant PA material that is highly flame retardant, crack-resistant, has excellent physical and mechanical properties, and is drip-proof. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a halogen-free flame-retardant nylon material, aiming to solve the problem of poor flame retardancy of the current PA material.

[0005] The above object of the present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a flame retardant nylon material. The raw materials of the halogen-free flame retardant nylon material include, by weight:

[0007] PA50-70 parts,

[0008] 1-5 parts of toughening agent,

[0009] 3-10 parts of P series flame retardant,

[0010] 3-10 parts of N series flame retardant,

[0011] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0012] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:

[0013]

[0014] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;

[0015] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

[0016] In some embodiments of the present invention, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group;

[0017] And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.

[0018] In some embodiments of the present invention, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

[0019]

[0020] In some embodiments of the present invention, the molar ratio of compound 1 to compound 2 is 2:1.

[0021] In some embodiments of the present invention, the method for preparing the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps:

[0022] Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist;

[0023] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;

[0024] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

[0025] In some embodiments of the present invention, the raw materials of the halogen-free flame-retardant nylon material include, by weight:

[0026] PA50-70 parts,

[0027] 1-5 parts of toughening agent,

[0028] 3-7 parts of P series flame retardant,

[0029] 3-7 parts of N series flame retardant,

[0030] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.

[0031] In some embodiments of the present invention, the toughening agent includes at least one of ethylene-octene copolymer, ethylene propylene copolymer, EMA, and EBA.

[0032] In some embodiments of the present invention, the P series flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate ester, phosphite, and phosphine oxide; and / or the N series flame retardant includes at least one of melamine urate, melamine phosphate, and melamine inorganic acid salt.

[0033] In some embodiments of the present invention, the raw material of the halogen-free flame-retardant nylon material further includes at least one of a lubricant and an antioxidant; wherein, based on the raw materials in parts by weight, the lubricant is 0.2-1 parts, and the antioxidant is 0.5-2 parts.

[0034] The second aspect of the present invention provides a method for preparing the above-mentioned halogen-free flame-retardant nylon material, comprising the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder to obtain a granular material, namely the flame-retardant nylon material.

[0035] In some embodiments of the present invention, the raw material further includes at least one of a lubricant and an antioxidant.

[0036] The flame retardant nylon material of the present invention includes PA, a toughening agent, a P-series flame retardant, an N-series flame retardant, and a modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. In the present invention, the PA material, the modified POSS and its derivative flame retardant synergist, the P-series flame retardant, and the N-series flame retardant are used together as the main components of the flame retardant nylon material, and the components cooperate and act synergistically with each other. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains a boron element, a ring structure R2 with a carbon-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores are decomposed by heat to form a dense ceramic barrier layer to isolate the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-hydrogen ratio greater than 1 R2 has a high carbon-to-hydrogen ratio. The benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glass-like protective film or a heat-insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures can form protective layers such as carbon layers, ceramic barrier layers, protective films or heat-insulating coke layers during the combustion process, which greatly improves the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. During the combustion process, the Si element and the C in the R2 group react with each other to form a protective layer. The element can react quickly to generate a large number of Si-C bonds, and the B element can form a glass film on the surface of the flame-retardant nylon material. The generated boric acid can quickly dehydrate the polymer to produce a carbon layer. The B element in the modified POSS and its derivative synergistic flame retardant can also coordinate with the P element in the system to produce a synergistic effect, thereby improving the flame retardant effect. By adding the modified POSS and its derivative synergistic flame retardant to work with the P and N series flame retardants, a harder carbon layer is quickly generated to prevent the flame retardant nylon from burning and dripping, and the air is isolated to improve the flame retardancy of the flame retardant nylon material. The P series flame retardant provides an acid source, and the N series flame retardant The agent provides a gas source, and the modified POSS and its derivative synergistic flame retardant provides a rich carbon source, so that the P series flame retardant and the N series flame retardant exert stronger flame retardancy, so that the prepared halogen-free flame retardant nylon material can ensure the original good processing performance, elasticity and flame retardancy of the thermoplastic elastomer, and improve the anti-cracking performance, flame retardancy and physical and mechanical properties of the halogen-free flame retardant nylon material. The modified POSS and its derivative flame retardant synergist is in the state of a colorless viscous liquid. When added to the halogen-free flame retardant nylon material, it has little effect on the performance of the flame retardant nylon material, and a halogen-free flame retardant nylon material with excellent flame retardancy can be obtained without a very high addition amount. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The molecular structure diagram of the modified POSS flame retardant synergist 1 of the present invention;

[0038] Figure 2This is a molecular structure diagram of the modified POSS flame retardant synergist 2 of the present invention. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0040] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.

[0041] PA: Polyamide, nylon, also known as polyamide fiber, is a general term for thermoplastic resins containing repeated amide groups (-NHCO-) ​​on the molecular chain, including aliphatic PA, aliphatic-aromatic PA and aromatic PA. Among them, aliphatic PA has many varieties and large output, and is mainly used in the automotive industry, electrical and electronic industry, transportation industry, machinery manufacturing industry and other fields to manufacture various bearings, gears, oil pipelines, oil storage tanks, protective covers and other parts.

[0042] EMA: ethylene-methyl acrylate copolymer, ethylene-methyl acrylate copolymer, is made by copolymerization of ethylene, methyl acrylate and auxiliary monomers. EMA has the characteristics of transparency, low density and elasticity, and also exhibits excellent waterproof performance, chemical stability, heat resistance and insulation performance. This material has a very wide range of applications, mainly in food packaging, pharmaceutical packaging, electronic and electrical equipment, construction and automotive parts.

[0043] EBA: Ethylene Butyl Acrylate, ethylene-butyl acrylate copolymer, is a high-performance polymer material with good reactivity, crystallinity and fluidity, good flexibility, high melting point, high thermal stability, good heat sealing performance, good low-temperature impact resistance, strong tolerance for pigments and inorganic fillers, and good compatibility with a variety of polymers. It is widely used in adhesives, food packaging, films, wires and cables, plastic modification and other fields.

[0044] POE: Polyolefin elastomer is a thermoplastic elastomer that is achieved by in-situ polymerization of ethylene and octene using a metallocene catalyst. It has excellent toughness, processability, weather resistance, heat aging resistance and UV resistance. Its molecular structure gives it a narrow relative molecular mass distribution and uniform short chain branching distribution, thus having excellent physical and mechanical properties (such as high elasticity, high strength, high elongation) and good low temperature performance.

[0045] PE: Polyethylene is a thermoplastic resin made from the polymerization of ethylene monomers, with excellent low temperature resistance and chemical stability. PE materials are widely used in various fields, including packaging, containers, pipes, wires and cables, etc. PE materials are often used in food packaging, cling film, water pipes, bubble bags, etc. due to their excellent chemical stability and wide applicability.

[0046] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.

[0047] Flame retardant nylon (PA) materials belong to a class of polymer materials with strong polarity. Hydrogen bonds can be formed between molecules, so the melting temperature is high, the melting temperature range is narrow, and there is a clear melting point. It is widely used in various industries. However, since nylon materials do not have flame retardant properties, flame retardant modification of nylon has become a new direction for nylon materials. At present, there are two main flame retardant modifications of nylon: chemical modification and physical modification. Chemical flame retardant modification is to introduce flame retardant components into the main chain or side chain of nylon through chemical reaction, so that the molecular chain itself can have flame retardant properties. Physical flame retardant modification is to introduce flame retardant components or flame retardants into the nylon matrix, and prepare flame retardant modified nylon materials through mixed granulation. Flame retardant modification by blending is the most convenient and widely used method. Flame retardant melamine polyphosphate (MPP) is a relatively ideal flame retardant for nylon. Its chemical composition elements are similar to nylon and it has good compatibility with the nylon matrix. At the same time, melamine polyphosphate molecules contain nitrogen and phosphorus elements, and have high flame retardant efficiency. Alkyl phosphinates, melamine polyphosphates, etc. are used as flame retardants, and nylon is used as the matrix through melt blending in an extruder to obtain flame retardant and antistatic nylon materials. Although this method can produce flame retardant and antistatic nylon, the amount of flame retardant melamine polyphosphate added is large, and the introduction of more flame retardants will reduce the mechanical properties of the material. Therefore, it is very necessary to develop a halogen-free PA material that is highly flame retardant, crack-resistant, has excellent physical and mechanical properties, and is drip-proof.

[0048] In order to solve the above problems, the first aspect of the present invention provides a halogen-free flame-retardant nylon material. The raw materials of the flame-retardant nylon material, measured in parts by weight, include:

[0049] PA50-70 parts,

[0050] 1-5 parts of toughening agent,

[0051] 3-10 parts of P series flame retardant,

[0052] 3-10 parts of N series flame retardant,

[0053] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0054] The structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:

[0055]

[0056] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;

[0057] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

[0058] It can be understood that when R1 connected to Si in the inorganic silicon cage core is a phenylene group, since the phenylene group contains a benzene ring, the carbon-to-hydrogen ratio and the carbon content of the benzene ring are relatively high. When burned, it works together with the large amount of Si contained in the inorganic silicon cage core to further improve the flame retardant properties of the inorganic silicon cage core, thereby improving the flame retardant properties of the modified polyhedral oligomeric silsesquioxane flame retardant synergist.

[0059] The halogen-free flame-retardant nylon material of the present invention comprises PA, a toughening agent, a P-series flame retardant, an N-series flame retardant and a modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. In the present invention, the PA material, the modified POSS and its derivative flame retardant synergist, the P-series flame retardant and the N-series flame retardant are used together as the main components of the flame-retardant nylon material, and the components cooperate and act synergistically with each other. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains a boron element, a ring structure R2 with a carbon-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores are decomposed by heat to form a dense ceramic barrier layer to isolate the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-hydrogen ratio greater than 1 Structure R2 has a high carbon-hydrogen ratio. The benzofuran group and polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glass-like protective film or a heat-insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or heat-insulating coke layers during the combustion process. The anti-drip effect is greatly improved. At the same time, it isolates heat and oxygen transfer and reduces the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. During the combustion process, the Si element and R2 The C element in the group can react quickly to generate a large number of Si-C bonds, and the B element can form a glass film on the surface of the flame-retardant nylon material. The generated boric acid can quickly dehydrate the polymer to produce a carbon layer. The B element in the modified POSS and its derivative synergistic flame retardant can also coordinate with the P element in the system to produce a synergistic effect, thereby improving the flame retardant effect. By adding the modified POSS and its derivative synergistic flame retardant to work with the P and N series flame retardants, a harder carbon layer is quickly generated to prevent the flame retardant nylon from burning and dripping, and the air is isolated to improve the flame retardancy of the flame retardant nylon material. The P series flame retardant provides acid The flame retardant nylon material prepared by the invention can ensure the original good processing performance, elasticity and flame retardancy of the thermoplastic elastomer, improve the anti-cracking performance, flame retardancy and physical and mechanical properties of the flame retardant nylon material, and the modified POSS and its derivative flame retardant synergist are in the state of colorless viscous liquid. When added to the flame retardant nylon material, it has little effect on the performance of the flame retardant nylon material, and does not require a very high addition amount to obtain a flame retardant nylon material with excellent flame retardancy.

[0060] Further, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.

[0061] The carbon-to-hydrogen ratio and carbon content in phenyl are both high, which can slow down the spread of flames during combustion. When the flame is removed, it can quickly extinguish itself, reducing the duration and intensity of combustion. The furan group has a high carbon content and contains oxygen elements that do not participate in combustion. The combination of the two forms a benzofuran group or dibenzofuran group that has both a high carbon-to-hydrogen ratio and a low combustion element. The two work together to form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air and prevent heat transfer, while reducing the content of combustibles and indirectly promoting carbonization.

[0062] In some embodiments, R2 is a benzofuranyl group.

[0063] In some embodiments, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group, and a perylene ring group.

[0064] The naphthalene ring group, anthracene ring group, phenanthrene ring group, acenaphthene ring group, fluorene ring group and perylene ring group have a relatively high carbon-hydrogen ratio and contain a large amount of carbon elements, which makes it easier to form a glass-like protective film or a heat-insulating coke layer when burned.

[0065] In some embodiments, R2 is a naphthyl ring group.

[0066] Furthermore, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

[0067]

[0068] Furthermore, in the above reaction process, the molar ratio of compound 1 to compound 2 is 2:1.

[0069] The spatial structure of compound 1 polyhedral oligomeric silsesquioxane is relatively large. In the reaction, it is necessary to ensure that compound 2 has a sufficiently small spatial steric hindrance so that it can react with compound 1 to obtain compound 3 modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. During the reaction, each compound 2 is connected to two compounds 1, that is, the molar ratio of compound 1 to compound 2 is 2:1, which ensures sufficient space for compound 3 and achieves structural stability of compound 3. Compound 2 contains two hydroxyl groups, and the two hydroxyl groups of one compound 2 are respectively combined with one amino group in two compounds 1 to undergo a dehydration reaction to obtain compound 3. The overall reaction requires a single substance, is simple to operate, and is easy to implement.

[0070] In some embodiments, compound 1 is aminopropyl heptaisobutyl caged polysilsesquioxane.

[0071] In some embodiments, compound 1 is aminophenyl heptaisobutyl caged polysilsesquioxane.

[0072] In some embodiments, compound 2 is benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid.

[0073] In some embodiments, compound 2 is dibenzofuran-4-boronic acid.

[0074] In some embodiments, the structural formula of compound 3 is:

[0075]

[0076] The following is designated as modified POSS flame retardant synergist 1.

[0077] In some embodiments, the structural formula of compound 3 is:

[0078]

[0079] The following is designated as modified POSS flame retardant synergist 2.

[0080] Furthermore, the preparation method of compound 3 comprises the following steps:

[0081] Compound 1 is dissolved in an organic solvent, and an aqueous solution of compound 2 is added under the action of a catalyst, and the mixture is subjected to a catalytic reaction, and then washed and dried to obtain compound 3;

[0082] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;

[0083] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

[0084] In some embodiments, the catalyst is acetic acid.

[0085] In some embodiments, the solvent is ethanol.

[0086] Furthermore, the raw materials of the flame retardant nylon material include, by weight:

[0087] PA50-70 parts,

[0088] 1-5 parts of toughening agent,

[0089] 3-7 parts of P series flame retardant,

[0090] 3-7 parts of N series flame retardant,

[0091] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.

[0092] Reducing the amount of P-series flame retardants and N-series flame retardants can further improve the mechanical properties of flame-retardant nylon materials.

[0093] Further, the toughening agent includes at least one of ethylene-octene copolymer, ethylene propylene copolymer, EMA, and EBA.

[0094] Toughening agents can increase the flexibility of the adhesive film layer and significantly increase the flexibility of the material, making it less likely to break under external force, improving the material's impact resistance and fatigue resistance, and effectively preventing the expansion of cracks, thereby extending the material's service life. They can weaken the interaction between the molecular chains of polymer materials, reduce the friction between the molecular chains, and increase the mobility of the polymer molecular chains, thereby improving the material's processing fluidity and molding performance.

[0095] It is understood that toughening agents include but are not limited to ethylene-octene copolymers, ethylene-propylene copolymers, EMA, and EBA.

[0096] Furthermore, the P series flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate ester, phosphite, and phosphine oxide; and / or, the N series flame retardant includes at least one of melamine urate, melamine phosphate, and melamine inorganic acid salt.

[0097] It is understood that the phosphorus-based flame retardant includes, but is not limited to, aluminum hypophosphite, calcium hypophosphite, diethyl aluminum phosphite, methyl ethyl aluminum hypophosphite and phenyl aluminum hypophosphite.

[0098] In some embodiments, the P-based flame retardant is preferably aluminum diethylphosphinate.

[0099] In some embodiments, the N-series flame retardant is preferably melamine cyanurate.

[0100] Furthermore, the raw materials of the flame retardant nylon material also include at least one of a lubricant and an antioxidant; wherein, the raw materials, in parts by weight, comprise 0.2-1 parts of lubricant and 0.5-2 parts of antioxidant.

[0101] In some embodiments, the antioxidant includes, but is not limited to, asymmetric hindered phenol antioxidants, aromatic amine antioxidants, thioether antioxidants, and phosphite antioxidants.

[0102] Hindered phenol antioxidants include, but are not limited to, antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), BHT (2,6-di-tert-butyl-p-cresol), and antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate);

[0103] Aromatic amine antioxidants include, but are not limited to, diphenylamine, p-phenylenediamine, and dihydroquinoline and their derivatives or polymers, such as: Antioxidant 445 (4,4'-bis(α.α-dimethylbenzyl)diphenylamine);

[0104] Thioether antioxidants include, but are not limited to, DLTP (dilauryl thiodipropionate), DSTDP (distearyl thiodipropionate), and DSTP (octadecyl thiodipropionate);

[0105] Phosphite antioxidants include, but are not limited to, antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 618 (pentaerythritol distearyl diphosphite), and antioxidant 626 (bis[2.4-di-tert-butylphenyl]pentaerythritol diphosphite).

[0106] By adding antioxidants, the anti-oxidation and anti-aging properties of polymer materials are improved, and the service life of polymer materials is extended.

[0107] In some embodiments, the lubricant includes but is not limited to PTFE powder, zinc stearate, magnesium stearate, silicone, calcium stearate or ethylene bis stearamide. By adding the lubricant, it is beneficial to promote a more uniform mixing of various raw materials, improve the fluidity of the polymer resin, reduce the friction coefficient, make the surface of the product smoother, improve the processing efficiency, and improve the transparency and gloss of the plastic.

[0108] In a second aspect, the present invention provides a method for preparing the flame retardant nylon material, comprising the following steps: uniformly mixing the raw materials, namely PA, toughening agent, P series flame retardant, N series flame retardant and modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, extruding and granulating through an extruder to obtain a granular material, namely a halogen-free flame retardant nylon material.

[0109] Furthermore, the raw material also includes at least one of a lubricant and an antioxidant.

[0110] The content of the present invention is explained below through specific examples and data.

[0111] The information of the raw materials involved in the specific implementation is shown in Table 1:

[0112] Table 1 Information of raw materials of Examples and Comparative Examples

[0113]

[0114]

[0115] The flame retardant nylon materials prepared in the examples and comparative examples were injection molded or pressed into sheets, and the flame retardant grade, oxygen index, tensile strength, and notched impact strength were tested. The test standards were as follows:

[0116] (1) Flame retardant grade test

[0117] In accordance with GB / T 5455-2014, the specimens are subjected to vertical burning grade test, the specimens are cut to the specified size and tested under conditions, and key parameters such as burning time limit and residual substances are monitored.

[0118] (2) Whether there is dripping when testing the flame retardant grade

[0119] Whether there is dripping when testing the flame retardancy level is tested according to the UL94 standard, the sample thickness is 3mm, and the test temperature is 23±2℃. The test is carried out using the UL94 vertical combustion test device of Jiangsu Zhengrui Taibang Electronics Co., Ltd.

[0120] (3) Oxygen index

[0121] According to GB / T 2406.2-2009, the sample size is prepared according to the type IV sample. The test is carried out according to method A-top surface ignition method. The test is carried out using the oxygen index tester device of Nanjing Jiangning District Fangshang Analytical Instrument Equipment Factory.

[0122] (4) Tensile strength

[0123] The test was conducted in accordance with Article 9 of GB 1040-2008, the test temperature was 23±2℃, and the tensile test used a standard dumbbell-shaped specimen with a tensile speed of 250mm / min. The tensile strength of 5 specimens was tested using a micro-controlled electronic universal material tensile machine from Dongguan High-speed Railway Testing Co., Ltd., and the results were averaged.

[0124] (5) Notched impact strength

[0125] The test was conducted in accordance with ISO 179-92. The sample was prepared according to the standard requirements and was usually in the shape of a rectangular parallelepiped. The key parameters were set. The impact velocity was usually set to 3.5 m / s, the pendulum energy could be selected to be 1 J, 2.75 J or 5.5 J, the pendulum lift angle was 150°, and the distance from the pendulum center to the impact blade was 335 mm. The test was repeated 5 times and the results were averaged.

[0126] The test results are shown in Table 3.

[0127] Embodiment 1:

[0128] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain a modified POSS flame retardant synergist 1;

[0129] 70 parts of PA, 5 parts of POE, 10 parts of modified POSS flame retardant synergist 1, 3 parts of diethyl aluminum hypophosphite, 3 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0130] Embodiment 2:

[0131] The preparation method is the same as that of Example 1, except that:

[0132] 50 parts of PA, 1 part of POE, 12 parts of modified POSS flame retardant synergist 1, 5 parts of diethyl aluminum hypophosphite, 3 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0133] Embodiment 3:

[0134] The preparation method is the same as that of Example 1, except that:

[0135] 70 parts of PA, 3 parts of POE, 2 parts of modified POSS flame retardant synergist 1, 3 parts of diethyl aluminum hypophosphite, 10 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0136] Embodiment 4:

[0137] The preparation method is the same as that of Example 1, except that:

[0138] 70 parts of PA, 4 parts of POE, 10 parts of modified POSS flame retardant synergist 1, 10 parts of diethyl aluminum hypophosphite, 9 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0139] Embodiment 5:

[0140] The preparation method is the same as that of Example 1, except that:

[0141] 70 parts of PA, 5 parts of POE, 12 parts of modified POSS flame retardant synergist 1, 7 parts of diethyl aluminum hypophosphite, 7 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0142] Embodiment 6:

[0143] The preparation method is the same as that of Example 1, except that:

[0144] 50 parts of PA, 1 part of POE, 12 parts of modified POSS flame retardant synergist 1, 7 parts of diethyl aluminum hypophosphite, 7 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0145] Embodiment 7:

[0146] The preparation method is the same as that of Example 1, except that:

[0147] 70 parts of PA, 4 parts of POE, 10 parts of modified POSS flame retardant synergist 1, 5 parts of diethyl aluminum hypophosphite, 5 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0148] Embodiment 8:

[0149] The preparation method is the same as that of Example 1, except that:

[0150] 73 parts of PA, 1 part of POE, 10 parts of modified POSS flame retardant synergist 1, 5 parts of diethyl aluminum hypophosphite, 5 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0151] Embodiment 9:

[0152] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of dibenzofuran-3-boric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain the modified POSS flame retardant synergist 2.

[0153] 70 parts of PA, 4 parts of POE, 10 parts of modified POSS flame retardant synergist 2, 5 parts of diethyl aluminum hypophosphite, 5 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0154] Comparative Example 1:

[0155] The preparation method is the same as that of Example 1, except that:

[0156] 70 parts of PA, 4 parts of POE, 14 parts of modified POSS flame retardant synergist 1, 3 parts of diethyl aluminum hypophosphite, 3 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0157] Comparative Example 2:

[0158] 70 parts of PA, 4 parts of POE, 10 parts of diethyl aluminum hypophosphite, 10 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame-retardant nylon prefabricated material, which is then dried at 80°C to obtain a highly flame-retardant and crack-resistant halogen-free flame-retardant nylon material.

[0159] Comparative Example 3:

[0160] The preparation method is the same as that of Example 1, except that:

[0161] 70 parts of PA, 4 parts of POE, 10 parts of modified POSS flame retardant synergist 2, 10 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0162] Comparative Example 4:

[0163] The preparation method is the same as that of Example 1, except that:

[0164] 70 parts of PA, 4 parts of POE, 10 parts of modified POSS flame retardant synergist 2, 10 parts of diethyl aluminum hypophosphite, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0165] Comparative Example 5:

[0166] The preparation method is the same as that of Example 10, except that:

[0167] 70 parts of PA, 4 parts of POE, 20 parts of modified POSS flame retardant synergist 2, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant and crack-resistant halogen-free flame retardant nylon material.

[0168] Comparative Example 6:

[0169] 70 parts of PA, 4 parts of POE, 20 parts of diethyl aluminum hypophosphite, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame-retardant nylon preform, and then dried at 80°C to obtain a highly flame-retardant and crack-resistant halogen-free flame-retardant nylon material.

[0170] Comparative Example 7:

[0171] 70 parts of PA, 4 parts of POE, 20 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame-retardant nylon prefabricated material, which is then dried at 80°C to obtain a highly flame-retardant and crack-resistant halogen-free flame-retardant nylon material.

[0172] Comparative Example 8:

[0173] 70 parts of PA, 4 parts of POE, 10 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant, 5 parts of diethyl aluminum hypophosphite, 5 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame-retardant nylon preform, and then dried at 80°C to obtain a highly flame-retardant and crack-resistant halogen-free flame-retardant nylon material.

[0174] Comparative Example 9:

[0175] 70 parts of PA, 4 parts of POE, 10 parts of aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, 5 parts of diethyl aluminum hypophosphite, 5 parts of MCA flame retardant, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a thermoplastic polyester elastomer flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyester elastomer flame retardant nylon material.

[0176] Comparative Example 10:

[0177] 70 parts of PA, 4 parts of POE, 5 parts of aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, 5 parts of aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, 5 parts of diethyl aluminum hypophosphite, 5 parts of MCA flame retardant, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a thermoplastic polyester elastomer flame retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyester elastomer flame retardant nylon material.

[0178] Comparative Example 11:

[0179] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of methylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain methylboric acid modified POSS flame retardant.

[0180] 70 parts of PA, 4 parts of POE, 10 parts of methyl boric acid modified POSS flame retardant, 5 parts of diethyl aluminum hypophosphite, 5 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame-retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame-retardant and crack-resistant halogen-free flame-retardant nylon material.

[0181] Comparative Example 12:

[0182] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of phenylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain phenylboric acid modified POSS flame retardant.

[0183] 70 parts of PA, 5 parts of POE, 10 parts of phenylboric acid modified POSS flame retardant, 5 parts of diethyl aluminum hypophosphite, 5 parts of MCA flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 260°C to obtain a flame-retardant nylon prefabricated material, and then dried at 80°C to obtain a highly flame-retardant and crack-resistant halogen-free flame-retardant nylon material.

[0184] The components and important preparation variables of Examples 1-9 and Comparative Examples 1-12 are summarized in Table 2. Table 2 Components of Examples 1-9 and Comparative Examples 1-12 of the present invention.

[0185] Table 2 Examples of the present invention and comparative examples

[0186]

[0187] According to the provisions of GB / T 1040-2008, GB / T 5455, GB / T 2406.2, UL94 and ISO 179-92, the flame retardant nylon materials in the above Examples 1-9 and Comparative Examples 1-12 were tested for tensile strength, flame retardancy, oxygen index, dripping during combustion and notched impact strength, and the test results were recorded in the following Table 3:

[0188] Table 3 Performance test table of Examples 1-9 and Comparative Examples 1-12 of the present invention

[0189]

[0190] It can be seen from Table 3 that the flame retardant nylon injection molded sheets of Examples 1-9 have high flame retardant properties, and the flame retardant grades all reach V0 level. There is no dripping in the V0 level test, and the oxygen index is all >25.By comparing Example 1 with Example 5, and Example 2 with Example 6, it can be seen that when the addition amount of P series flame retardant and N series flame retardant is increased, the flame retardant properties of the prepared flame retardant nylon material are improved, but the tensile strength and notched impact strength are reduced, indicating that too much flame retardant can improve the flame retardant properties of the material, but it will also cause the physical and mechanical properties of the material matrix to decrease, resulting in poor plastic deformation ability of the prepared material and easy fracture; by comparing Example 7 with Example 9, what is changed is the structural type of the added modified POSS flame retardant synergist. By comparing the experimental data in the above table, the tensile strength, flame retardant grade, oxygen index, whether it drips during combustion and notched impact strength of Example 7 and Example 9 are different. The test results are basically the same, indicating that in the present invention, the change of the substrate in the system and the change of the type of modified POSS flame retardant synergist will not affect the performance of the prepared thermoplastic polyester elastomer material; in Comparative Example 1, relative to Example 7, an excessive amount of modified POSS flame retardant synergist 1 is added, and the physical and mechanical properties and flame retardant properties of the prepared flame retardant nylon material are reduced instead. When an excessive amount of modified POSS flame retardant synergist is added, an effective flame retardant system can not be formed with P series flame retardant and N series flame retardant, which reduces the physical and mechanical properties of the system and also causes the poor plastic deformation ability of the prepared material; in Comparative Examples 2-7, the number of modified POSS flame retardant synergist, P series flame retardant and N series flame retardant added is changed, and it can be obtained It is found that when the system lacks any one of the modified POSS flame retardant synergist, the P series flame retardant and the N series flame retardant, the flame retardant properties of the prepared flame retardant nylon material will be reduced, and dripping phenomena of varying degrees will occur during the combustion process, and its physical and mechanical properties are also poor. It is clear that in the present invention, the modified POSS flame retardant synergist, the P series flame retardant and the N series flame retardant need to work together to form a glass film and a carbon layer on the surface of the material, thereby improving the flame retardant effect, achieving the effect of anti-drip during combustion and being able to improve the physical and mechanical properties of the material. In comparative examples 8-10, the modified POSS flame retardant synergist is changed into its reactant, and the experimental data of the three cannot achieve the effect of anti-drip during combustion, and the flame retardant properties of comparative example 9 are poor. In Comparative Example 11 and Comparative Example 12, the same number of methylboric acid modified POSS flame retardant synergist and phenylboric acid modified POSS flame retardant synergist are added respectively to replace the modified POSS flame retardant synergist of the present invention. The methylboric acid modified POSS flame retardant synergist lacks the R2 group with a carbon-hydrogen ratio greater than 1, and the phenylboric acid modified POSS flame retardant synergist contains a benzene ring structure. However, the flame retardant grade of Comparative Example 11 is V2, and the anti-drip effect cannot be achieved during combustion. The flame retardant performance in Comparative Example 12 is higher, and the anti-drip effect cannot be achieved during combustion, indicating that the modified POSS flame retardant synergist containing a benzene ring structure cannot generate an effective char layer during the combustion process to achieve the anti-drip effect during combustion.

[0191] Therefore, the present invention verifies that the flame retardancy of the flame retardant nylon material is improved by modifying the POSS flame retardant synergist, so that the material has excellent physical and mechanical properties and excellent combustion and dripping prevention effects, has extremely high industrial value, and can be widely used and promoted.

[0192] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A flame retardant nylon material, characterized in that: The raw materials of the halogen-free flame-retardant nylon material include, by weight: PA50-70 parts, 1-5 parts of toughening agent, 3-10 parts of P series flame retardant, 3-10 parts of N series flame retardant, 2-12 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is: Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

2. The halogen-free flame-retardant nylon material according to claim 1, characterized in that: The benzofuran group includes at least one of a benzofuran group and a dibenzofuran group; And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.

3. The halogen-free flame-retardant nylon material according to claim 1, characterized in that: The modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

4. The halogen-free flame-retardant nylon material according to claim 3, characterized in that: The molar ratio of compound 1 to compound 2 is 2:

1.

5. The halogen-free flame-retardant nylon material according to claim 3, characterized in that: The preparation method of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps: Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist; Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives; The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

6. The halogen-free flame-retardant nylon material according to claim 1, characterized in that: The raw materials of the flame retardant nylon material include, by weight: PA50-70 parts, 1-5 parts of toughening agent, 3-7 parts of P series flame retardant, 3-7 parts of N series flame retardant, 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.

7. The halogen-free flame-retardant nylon material according to claim 1, characterized in that: The toughening agent includes at least one of ethylene-octene copolymer, ethylene-propylene copolymer, EMA and EBA.

8. The halogen-free flame-retardant nylon material according to claim 1, characterized in that: The P series flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphine oxide; And / or, the N series flame retardant includes at least one of melamine urate, melamine phosphate, and melamine inorganic acid salt.

9. The halogen-free flame-retardant nylon material according to claim 1, characterized in that: The raw materials of the flame retardant nylon material also include at least one of a lubricant and an antioxidant; wherein, in terms of weight, the lubricant is 0.2-1 parts, and the antioxidant is 0.5-2 parts.

10. A method for preparing a halogen-free flame-retardant nylon material as claimed in claim 1, characterized in that: The method comprises the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder, and obtaining granular materials, namely the flame-retardant nylon material.

11. The method for preparing a halogen-free flame-retardant nylon material according to claim 10, characterized in that: The raw material also includes at least one of a lubricant and an antioxidant.

Citation Information

Patent Citations

  • Polyhydroxyalkylphenyl polysilsesquioxane and preparation method and application thereof

    CN106750308A

  • Preparation method and application of organic-inorganic hybrid carbonizing agent of polyphosphazene modified titanium carbide nanosheet

    CN115838496A

  • Organic silicon-boron flame retardant as well as preparation method and application thereof

    CN115974908A

  • Synthetic method for constructing antibacterial coating with polyboronic acid groups on surface of substrate

    CN118422507A

  • Hardener compound for epoxy system

    WO2014089788A1

Cited By

  • Flame-retardant anti-aging PA6T material as well as preparation method and application thereof

    CN121450098A

  • Modified POSS flame-retardant regenerated polyester fiber and preparation method thereof

    CN121538755A